KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS THE CARE OF EPILEPTIC PATIENTS BY THEIR CARETAKERS ATTENDING THE OUTPATIENT DEPARTMENT IN KAPCHORWA HOSPITAL, KAPCHORWA DISTRICT. A CROSS-SECTIONAL STUDY. - Kisa, Joy; Atukuma, Cliffe (Student's Journal of Health Research Africa, 2024)
Background: The specific objectives were to determine the knowledge, and assess attitudes towards the care of epileptic patients among their caretakers, and to explore the common treatment practices done by the caretakers of epileptic patients attending outpatient departments in Kapchorwa Hospital, Kapchorwa District. Methodology: A facility-based cross-sectional study that involved both quantitative and qualitative methods was used. 50 respondents were selected using simple random sampling and interviewed using a questionnaire with closed-ended questions. Results: The majority (56%) of the respondents were aged >35, female (64%), Sabinys (84%), Majority (84%) of the participants had heard about epilepsy and more than half (58%) didn’t know about the cause of epilepsy. The majority (96%) of them could recognize when their patients got an attack, less than half (46%) reported that loss of consciousness helped them notice an attack among their patients and less than half (40%) reported that emotional distance made their patients get an attack. The majority (64%) of the participants reported that epileptic patients are normal people, the majority (60%) reported their patients should not be employed, less than half (48%) rushed their patients to the hospital and most (36%) reported lying their patient down as the first aid they gave. Conclusion: Knowledge of the care of epileptic patients by their caretakers was fairly satisfactory their attitude and practices towards the care of epileptic patients were most likely to expose their patients to some degree of stigma and low self-esteem due to their belief that they are mad people, should not be employed nor get married. Recommendations: Health workers attending to epileptic patients and their caretakers at the outpatient department of Kapchorwa Hospital should continue to health educate caretakers to increase awareness about the cause, symptoms, and treatment options for epileptic patients and to decrease the negative attitude of the community.